(untitled) (New York, 1984)
Scientific research and technological progress are key factors in determining productivity, comparative advantage, patterns of production, the prospects for trade and the possibility of adjustment for both developed and developing countries.
Keywords: Science and state,Technology and state,Nhà nước và khoa học,Nhà nước và công nghệ; Congresses,Congresses,Hội nghị,Hội nghị; China,China,Trung Quốc,Trung Quốc